2019
DOI: 10.21307/pjm-2019-013
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Outbreaks in Khyber Pakhtunkhwa (KPK), Pakistan in 2017: An Integrated Disease Surveillance and Response System (IDSRS)-Based Report

Abstract: The current study is a retrospective epidemic report regarding dengue fever (DF) virus infection cases (2017) from fifteen districts of KPK, Pakistan. Medical records of 120 948 patients were reviewed retrospectively for demographic, clinical and laboratory data. The presence of dengue infection was confirmed by NS1-ELISA and RT-PCR, respectively. The total positive cases (of suspected DF samples) were 24 938 (20.6%), whereas seventy cases (0.28%) had a fatal outcome. Mean age ± SD of the dengue patients was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
(13 reference statements)
3
24
0
Order By: Relevance
“…In our study, we found that around more than half of the patients (55.4%) were older than 35 years, which is consistent with earlier reports from the southern part of the country [ 16 ]. In the hyperendemic areas of India, a large cohort of test-positive dengue patients had a median age of 25 years [interquartile range (IQR) = 16-36 years] [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that around more than half of the patients (55.4%) were older than 35 years, which is consistent with earlier reports from the southern part of the country [ 16 ]. In the hyperendemic areas of India, a large cohort of test-positive dengue patients had a median age of 25 years [interquartile range (IQR) = 16-36 years] [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…With powerful cooperative reaction from government and Nongovernmental Organizations (NGOs), healthcare professionals are helping to prevent further spread of the epidemic [24]. Public awareness about the seasonal epidemic outbreaks, especially regarding dengue fever, actual problem understanding, and the approaches to monitor dengue outbreaks are significant considerations.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, it is an important need of the present day automated surveillance systems to use data from EHR. For example, Integrated Disease Surveillance and Response System (IDSRS) requires data to be obtained from patient medical records [77], [78].…”
Section: B Public Health Surveillancementioning
confidence: 99%